Electrical contact resistance research of graphite with copper and termo-expanded graphite - Карвацкий, Антон Янович; Лелека, Сергей Владимирович; Пулинец, Игорь Валериевич; Лазарев, Тарас Валериевич; Педченко, Анатолий Юрьевич (Eastern-European Journal of Enterprise Technologies, 2014)
The experimental setup for measuring the specific electrical contact resistance (SECR) of solids contact pairs, depending on the compression pressure and temperature, has been developed. In the development of graphitization furnaces numerical models the electrical properties of the contact interaction of copper-graphite, graphite-graphite, using a gasket of thermo-expanded graphite, are important. Resistance of the contact portions is always greater than the contacting elements, thus, there are additional losses of energy in these regions. This affects the thermoelectric state of furnaces. The relevance of this study is determined by the absence of data concerning the contact resistance of graphite-gasket- graphite in the literature. The most difficult task in the investigation of the contact resistance transition is to determine the actual contact area, the value of which depends on the nature of the microscopic bulge deformation. The theoretical solution to the problem concerning the actual contact area of real surfaces is very difficult, that is why experimental methods have become widespread in the study of the electrical solids contact resistance. As a result of research, the following experimental data was observed: SECR of the copper-graphite at compression pressure of 1 – 7 MPa and under the temperature 16 С; SECR of the graphite-gasket-graphite at constant pressure of 1,7 MPa under the temperature range 16 – 250 С with subsequent extrapolation to 3000 С. The experimental data of the SECR contact pairs of copper-graphite and graphite-gasket-graphite is necessary for the priori estimation of graphitization furnace thermoelectric state during their development, modernization and also for electrothermal equipment of other industries.